Improving inter-professional collaborations: Multi-agency working for children's wellbeing - Edwards, A; Daniels, H; Gallagher, T; Leadbetter, J; Warmington, P (Routledge Taylor and Francis Group, 2009)
Shortlisted for the NASEN Special Educational Needs Academic Book Award 2009. Inter-professional collaborations are invaluable relationships which can prevent the social exclusion of children and young people and are now a common feature of welfare policies worldwide. Drawing on a four year study of the skills and understanding required of practitioners in order to establish the most effective interagency collaborations, this comprehensive text. Gives examples from practitioners developing inter-professional practices allow readers to reflect on their relevance for their own work Emphasises what needs to be learnt for responsive inter-professional work and how that learning can be promoted Examines how professional and organisational learning are intertwined Suggests how organisations can provide conditions to support the enhanced forms of professional practices revealed in the study Reveals the professional motives driving the practices as well as how they are founded and sustained Full of ideas to help shape collaborative inter-professional practice this book shows that specialist expertise is distributed across local networks. The reader is encouraged to develop the capacity to recognise the expertise of others and to negotiate theor work with others. This book is essential reading for practitioners in education and educational psychology or social work, and offers crucial insights for local strategists and those involved in professional development work. The book also has a great deal to offer researchers working in the area of cultural historical activity theory (CHAT). The four year study was framed by CHAT and offers a well-worked example of how CHAT can be used to reveal sense-making in new practices and the organizational implications of enhanced professional decision-making. As well as being important contributors to the developing CHAT field, the five authors have worked in the area of social exclusion and professional learning for several years and have brought inter-disciplinary strengths to this account of inter-professional work.